Pola Pendidikan Humanis Religius pada Rumah Pintar âPijoenganâ Bantul Yogyakarta - Munjahid, Munjahid; Kuswanto, Heri (IAIN Ponorogo, 2018)
The academic anxiety in this paper is the number of educational processes deviating from its primary mission of humanizing humans. The learning process focuses only on try out and discussion of exam questions while the formation of attitudes and skills is ignored. The formulation of the problem in this article is: What is the pattern of religious humanist education in Rumah Pintar